A multiagent approach for detecting and mitigating DDoS attacks - Pereira, João P. A.; Simplicio Jr., Marcos A.; Brandão, Anarosa A. F. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2013)
This paper describes Arquitena, a multiagent approach for detecting and mitigating DDoS attacks in Internet Services Providers (ISP) networks. Arquitena’s main property is to identify situations that characterize attack scenarios, such as a large stream of packets directed to a network service or equipment. This is accomplished by using a virtual network of agents that mirrors the actual network infrastructure, which tends to facilitate the detection of attack routes, identification of malicious traffic and protection of hypothetical victims. Together with the system’s description and rationale, we describe our preliminary prototype that will be employed for its evaluation.